Behind the Bench: Power Dynamics in the Supreme Court of the United States Through the Lens of Construal Level - Chang, Mykaela L. (Advances in Social Sciences Research Journal, 2024)
Power dynamics exist among the nine justices on the Supreme Court. Through the lens of construal level, the justices’ psychological distance can indicate power, which can ultimately affect the decision-making process on case deliberation. This research examines power dynamics arising from tenure, gender, and political ideology of the justices, and the type of opinion written, through language conveyed in written opinions. I find that tenure, gender and political ideology have some association with abstraction, certainty, positive affect and/or future orientation, suggesting that justices have predictable behavioral implications stemming from their power level. Results for the type of opinions show significance for the opposite prediction, with concurring and dissenting opinions exhibiting more abstract, certain and positive. Exploring power dynamics among the justices helps to unpack the decision-making process in the High Court.